Scientific literature addressing detection of monosialoganglioside A 10-year bibliometric analysis - Xu, Yanli; Li, Miaojing; Liu, Zhijun; Xi, Aiping; Zhao, Chaoxian; Zhang, Jianzhong (Neural regeneration research, 2012)
OBJECTIVE： The study was undertaken to explore a bibliometric approach to quantitatively assess the research on detection of monosialoganglioside from 2002 to 2011. DATA RETRIEVAL： A bibliometric analysis based on the publications on Web of Science was performed using key words such as ＂monosialoganglioside＂, ＂colloidal gold＂, ＂high performance liquid chromatography＂ and ＂detection＂. SELECTION CRITERIA： （1） Research articles on the detection of monosialoganglioside; （2） researches on human and animal fundamentals, clinical trials and case reports; （3） article types： article, review, proceedings paper, note, letter, editorial material, discussion, book chapter; （4） Publication year： 2002-2011. Exclusion criteria： （1） unrelated articles; （2） type of articles： correction; （3） articles from following databases： all databases related to social science and arts ＆ humanities in Web of Science were excluded. MAIN OUTCOME MEASURES： （1） distribution of subject areas; （2） number of publications annually; （3） document type and language of publications; （4） distribution of institutions; （5） distribution of output in journals; （6） the number of countries in which the article is published; （7） top cited paper. RESULTS： Overall population stands at 1 880 research articles addressing detection of monosialoganglioside in Web of Science during the study period. Articles （1 599） were the most frequently used document type comprising 85.05%, followed by meeting abstracts, reviews and proceedings papers. The distribution of subject categories showed that monosialoganglioside research covered both clinical and basic science research. The USA, Japan, and Italy were the three most productive countries, and the publication numbers in the USA were highest with 559 papers. The University of Milan, Nagoya University, and Kinki University are the most productive institutions regarding detection of monosialoganglioside. In 559 articles published by Americans, Medical College of Georgia ranked the first with 30 articles, followed by University of Medicine and Dentistry of New Jersey （28 articles）, Cornell University （24 articles） and Johns Hopkins University （24 articles）. In 442 articles published by Japanese, Nagoya University ranked the first with 40 articles, followed by Kinki University （36 articles）, and Dokkyo University （31 articles）. Though the total number of publications by Japanese is smaller than Americans, the top three institutions published more publications than American institutions. There is a markedly increase in the number of publications on the subject detection of monosialoganglioside in 2004, which the peak in the past 10 years. The valley bottom of the subject appeared in 2005. In total, the research is increased with time prolonged. Journal of Neurochemistry, Journal of Biological Chemistry and Journal of Neuroimmunology were core subject journals in monosialoganglioside studies. CONCLUSION： This study highlights the topics in detection of monosialoganglioside research that are being published around the world.